2006
DOI: 10.1111/j.1539-6924.2006.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Place, Culture, and the Social Amplification of Risk

Abstract: This article investigates the role of culture in the social production of risks and risk communication surrounding industrial development in a region located at a rural-urban interface. A case study examined a public consultation that was undertaken to inform local residents about an eco-industrial development proposal being planned near Edmonton, Alberta, Canada. The research employed the social amplification of risk framework (SARF) to examine the relationships among culture, place, and socially constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 43 publications
3
94
0
3
Order By: Relevance
“…These perceptions are likely to be filtered through values and meanings attached to whatever is under threat and some argue that attachments to a place or locale are likely to be particularly influential (Masuda and Garvin 2006;Venables et al 2012). Such emotional attachments (Tuan 1974) are often characterized as place identity and place dependence.…”
Section: Introductionmentioning
confidence: 99%
“…These perceptions are likely to be filtered through values and meanings attached to whatever is under threat and some argue that attachments to a place or locale are likely to be particularly influential (Masuda and Garvin 2006;Venables et al 2012). Such emotional attachments (Tuan 1974) are often characterized as place identity and place dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Some are qualitative, analyzing rich verbal accounts among the public from interviews (for example Masuda and Garvin, 2006) and discussion groups (Petts and Niemeyer, 2004;Busby and Duckett, 2012), or analysing media content (Bakir, 2005). These have revealed how the worldview of individuals affects their tendency to amplify risk, and how particular actors use the media to convey their view of the risk and influence opinion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Externally introduced risks serve to disrupt these aspects of place-identity, and result in heightened anxiety about risks associated with these changes. Masuda and Garvin (2006) showed that place is an important component in the social 204 C.G. Jardine et al…”
Section: Sociocultural and Place Influences On Riskmentioning
confidence: 99%
“…Previous studies have also shown that knowledge and understanding of risk are strongly associated with culture and different ways of knowing, and that context and situation are critical to understanding how people view and respond to risk (Krimsky and Plough 1988;Satterfield et al 2004). Similarly, responses to risks have been shown to be related to connections to 'place' and 'place-identity' (Wester-Herber 2004;Masuda and Garvin 2006). Both gendered attributes (McDowell 1999) and risk perspectives (Kasperson et al 1988; are acknowledged to be 'socially constructed' in that they are created and developed by society and/or through social and cultural practices.…”
Section: Introductionmentioning
confidence: 99%